580 INCIDENCE AND FACTORS ASSOCIATED WITH DE NOVO ATRIAL FIBRILLATION IN PATIENTS WITH WILD-TYPE TRANSTHYRETIN CARDIAC AMYLOIDOSIS - A MULTICENTER STUDY. (15th December 2022) - Fumagalli, Carlo; Zampieri, Mattia; Argirò, Alessia; Musumeci, Beatrice; Tini, Giacomo; Di Bella, Gianluca; Cipriani, Alberto; Porcari, Aldostefano; Canepa, Marco; Merlo, Marco; Sinagra, Gianfranco; Rapezzi, Claudio; et al.
Abstract: Purpose: We described the incidence and ECG factors associated with de novo atrial fibrillation (AF) in patients diagnosed with wild-type transthyretin cardiac amyloidosis (ATTRwt-CA) to drive tailored arrhythmia screening. Background: Data on the incidence rate and factors associated with de novo AF in patients with ATTRwt CA is limited. Methods: Multicenter, retrospective, observational cohort study performed in six referral centers for CA. All consecutive patients diagnosed with ATTRwt-CA between 2004 and 2020 with >1-year follow up (FU) were enrolled in the study and were divided into three groups according to presence of AF: (1)patients with 'known AF'; (2)patients in 'sinus rhythm' and (3)patients developing 'de novo AF' during FU. Incidence and factors associated with AF in patients with ATTRwt were the primary outcomes. Results: Overall, 266 patients were followed for a median of 469 days: 148 (56%) with known AF, 84 (31.6%) with sinus rhythm, and 34 (12.8%) with de novo AF. Age and gender were similarly distributed. At multivariable analysis, PR (Hazard Ratio[HR]: 1.008 95% C.I. 1.001-1.016), QRS (HR: 1.022 95% C.I. 1.002-1.043) and left atrial dilatation>50mm (HR: 3.429 95% C.I. 1.565-7.329) were associated with de novo AF at FU. Patients presenting with at least two risk factors (PR>200ms, QRS>120ms or LAD>50mm) had a higher risk of developing de novo AF compared to patients with no risk factors (HR 14.918 95% C.I. 3.242-31.646). Conclusions: Incidence of de novo AF in patients with ATTRwt is 20.7%/year. Longer PR and QRS duration and left atrial dilation are associated with arrhythmia onset.